2019
DOI: 10.1038/s41419-019-1324-8
|View full text |Cite
|
Sign up to set email alerts
|

MPC1 deficiency accelerates lung adenocarcinoma progression through the STAT3 pathway

Abstract: Mitochondrial pyruvate carrier 1 (MPC1), a key factor that controls pyruvate transportation in the mitochondria, is known to be frequently dysregulated in tumor initiation and progression. However, the clinical relevance and potential molecular mechanisms of MPC1 in lung adenocarcinoma (LAC) progression remain to be illustrated. Herein, MPC1 was lowly expressed in LAC tissues and significantly associated with favorable survival of patients with LAC. Functionally, MPC1 markedly suppressed stemness, invasion, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
(38 reference statements)
1
26
0
Order By: Relevance
“…Moreover, MPC inhibition conferred on these cells the ability to migrate and an increased resistance to both chemotherapy and radiotherapy [87,91,93]. Similar observations were reported for lung adenocarcinomas [90]. Taken together, these results highlight a role of MPC in determining the stemness status of cancer cells in vitro.…”
Section: The Role Of Mpc In Stemnesssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, MPC inhibition conferred on these cells the ability to migrate and an increased resistance to both chemotherapy and radiotherapy [87,91,93]. Similar observations were reported for lung adenocarcinomas [90]. Taken together, these results highlight a role of MPC in determining the stemness status of cancer cells in vitro.…”
Section: The Role Of Mpc In Stemnesssupporting
confidence: 80%
“…As described above, cancer cells in vitro rely mainly on aerobic glycolysis for rapid cell growth (Figure 3), and it is not surprising, therefore, that loss of MPC expression, which favors increased glycolysis, was found to be associated with poor cancer prognosis [85][86][87][88][89][90]. One of the main questions in the field is whether loss of functional MPC can initiate tumorigenesis and, conversely, whether increasing MPC activity would result in reduced aerobic glycolysis.…”
Section: The Role Of Mpc In Cancermentioning
confidence: 91%
“…For one of these methylation traits, cg06249499, we also found that increased levels of measured methylation were associated with increased FEV 1 among MESA participants. MPC1 (mitochondrial pyruvate carrier 1) plays a role in transport of pyruvate into mitochondria and down regulation of MPC1 has been shown to accelerate progression of lung adenocarcinoma 44 . Like RGN, MPC1 is also a member of the phosphorus metabolic process gene ontology term, suggesting further study of this pathway is warranted in relation to COPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to normal cells, cancer cells are more likely to shift from mitochondrial oxidative phosphorylation to aerobic glycolysis, such phenomenon is called "Warburg effect" (25). "Warburg effect" requires the downregulation of BRP44L in cancer cells and the BRP44L levels are relatively low in several cancer types, including lung cancer (26,27). Although cancer cells do not mainly rely on the TCA cycle to generate ATP, it still requires the TCA cycle to produce the intermediates for the synthesis of nucleic acids, fatty acids, and carbon skeleton (28).…”
Section: Discussionmentioning
confidence: 99%